EFFECT OF THE STRATEGY OF THE IMPACT OF DIDACTIC IN THE COLLECTION OF FIFTH GRADE STUDENTS IN THE SUBJECT OF QURAN AND ISLAMIC EDUCATION - Assistant Lecture Athraa Najy Abd (Scholars Digest Publishing, 2024)
The aim of this study was to investigate the effect of teaching contract strategy on the academic performance of fifth grade students in Quran and Islamic education. In light of the above, the following hypothesis is hereby posited: There is no statistically significant difference at the .05 level between the mean score of fifth-grade students (experimental group) taught with the teaching contract strategy and the mean score of fifth-grade students (control group) taught with the traditional teaching method in the final examination. With the second-semester approach, the hypothesis is tentatively tried under incomplete control through an experiment. A final test was conducted to measure the performance of the students. The sample of the study included fifth-grade students at Baghdad Education Directorate/Kaher Second Day School. This class was randomly split into two groups. One of them represented the experimental group (40 students) who were taught with the teaching contract strategy and the other represented the control group (34 students) who were taught with the traditional method. A comparison was made between the two groups on the bases of intelligence, age, parents’ education level, and previous year grades. The researcher developed a test consisting of 40 items: 19 multiple choice questions, 10 fill-in-the-blanks questions, and 11 short answer questions. Both groups of students were taught by the researchers in person. After the experiment, data were analyzed statistically by researchers. The results of the achievement test indicated that the experimental group of students outperformed the control group of students. On the grounds of these results, the researchers put forward a number of recommendations and conclusions.
Keywords: Didactic Contract Strategy, Academic Achievement, Fifth Grade, Female Students, Islamic Education